Lichen Herbarium of the Institute of Marine Geology and Geophysics of the FEB RAS (SAK): preliminary results of the inventory - Ezhkin, Alexander K.; Kaganov, Vladimir V. (Геосистемы переходных зон, 2024)
The organization of the lichen herbarium in the Institute of Marine Geology and Geophysics of the FEB RAS was initiated in 2014 after a number of integrated expeditions in the Sakhalin Region. The herbarium is based on the collections of Aleksander K. Ezhkin and Vladimir V. Kaganov. A significant amount of lichen samples was collected in protected areas of the Sakhalin Region, in wild remote sites, and in areas of volcanic activity. Currently, a part of the collection (1178 samples, 307 species) is mounted and stored in the Laboratory of plant ecology and geoecology, which is about 1/8 of all herbarium material of lichens stored in the Institute of Marine Geology and Geophysics of the FEB RAS.